Outcome of vesicourethral anastomosis after robot-assisted laparoscopic radical prostatectomy: A 6-year experience in Taiwan - Cheng-Che Chen; Cheng-Kuang Yang; Siu-Wan Hung; John Wang; Yen-Chuan Ou (Journal of the Formosan Medical Association, 2015)
The use of a da Vinci robotic system may improve the outcome of urological surgery. This study reports 6 years of experience with vesicourethral anastomosis (VUA) following robot-assisted laparoscopic radical prostatectomy (RALP) performed in Taichung Veterans General Hospital, Taichung, Taiwan. Methods: A total of 350 patients who underwent RALP by a single surgeon were reviewed. We followed Dr Patel's RALP procedure with minor modifications. VUA was checked with 120 mL and 200 mL saline in sequence. The urinary bladder was then pressed with endoscopic instruments. If a VUA leak was detected, it was sutured immediately. An 18-French silicon Foley's catheter was inserted and removed 7–14 days after RALP. Preoperative characteristics and perioperative complications were assessed. Results: Overall, 332 (94.85%) patients were without any leakage in the first step of the challenge, eight of whom had leakage in the second step. After repair, all were free from leakage. The other 18 patients had leakage in the first step of the challenge (5.14%). After repair, 12 patients were without leakage in the second step. However, one patient had urine leakage postoperatively. The other six patients had leakage in the second step. After repair, two patients were free from leakage, but the remaining four suffered from persistent minor urine leakage postoperatively. The urine leakage rate after RALP was 1.43% (5/350). The potential urine leakage after bladder challenge and endoscopic instruments pressing could be minimized to 0.29% (1/346). Conclusion: VUA leakage after RALP is rare. Intraoperative VUA challenge is simple and feasible compared to postoperative retrograde cystography.